Virtual tour-based digital batik village as a place for promotion of Bekasi city batik in the industry 4.0 era: Study on batik tiara - Agung Sudjatmoko; Azani Cempaka Sari; M. Maryani (Journal of Community Service and Empowerment, 2023)
The development of digital technology and virtual reality has also given birth to virtual tourism innovations that impact improving the community's economy through training. This program is carried out to create virtual tourist villages, mainly based on virtual batik tourism so that batik artisans have more time to promote their products and the tourist aspect. The virtual tour-based batik village aims to make the batik artisan community more active in utilizing digital application platforms to market their products and produce practical marketing applications. This digital application makes it easier for buyers to find out the promotions being carried out by Bekasi batik by utilizing gadgets and taking advantage of the digital world. The training method uses a case study approach, discussion, and lecture and ends with a training evaluation. The results of the study are based on the review of the user experience of Bekasi city batik artisans; out of 50 respondents, it is found that 55% strongly agree that training materials and virtual tour systems that are socialized are easy to access, can develop digital village web-based virtual tours as well as a forum for urban batik promotion Bekasi. In the aspect of the desired goals of the Bekasi city batik artisans participants, out of 50 respondents, the result was that 65% strongly agreed that the learning objectives of the training and virtual tour system met the expectations of the respondents. It is the hope of the training participants that the problem of marketing the virtual tour system will be a solution to expand the marketing of batik in the City of Bekasi.